2009
DOI: 10.1308/003588409x358999
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of the Use of the Jones' Intestinal Tube in Adhesive Small Bowel Obstruction

Abstract: INTRODUCTION Intestinal intubation with a Jones' tube has been suggested to reduce the incidence of recurrent adhesive bstruction. This paper describes our experience of this technique. PATIENTS AND METHODS A retrospective case-note review was performed on 68 patients admitted to a teaching hospital who re identified as having had the Jones' intestinal tube placed over an 11-year period from 1980 to 1991, with a follow-up to 2003. The indication for placement and outcome following placement of the tube were do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…The cornerstone of non-operative management is nil per os and decompression using a naso-gastric tube or long intestinal tube. Non-operative management is effective in approximately 70–90% of patients with ASBO [ 1 , 75 , 76 ]. There has been some debate in the literature over the use of long intestinal tubes or naso-gastric tubes.…”
Section: Resultsmentioning
confidence: 99%
“…The cornerstone of non-operative management is nil per os and decompression using a naso-gastric tube or long intestinal tube. Non-operative management is effective in approximately 70–90% of patients with ASBO [ 1 , 75 , 76 ]. There has been some debate in the literature over the use of long intestinal tubes or naso-gastric tubes.…”
Section: Resultsmentioning
confidence: 99%
“…The strategy of long intestinal tube splinting is based on acknowledging the possibility of the formation of adhesions and fixing the bowel so as to ensure a favorable lie and thereby prevent the recurrence of ASBO. In patients having ASBO with multiple matted adhesions, long intestinal tube splinting has been shown to decrease the recurrence rate of ASBO [ 18 ]. Our study clearly showed that the recurrence rate of ASBO in the tube splinting group was lower than that in the simple adhesiolysis group (6.7% vs. 40%, P = 0.02).…”
Section: Discussionmentioning
confidence: 99%
“…1,3 Cases of obstructing extensive fibrous adhesions often require a non-orthodox surgical solution.…”
Section: Discussionmentioning
confidence: 99%